Mechanism of Mer receptor tyrosine kinase inhibition of glomerular endothelial cell inflammation. Issue 4 (19th January 2018) - Zhen, Yuxuan; Finkelman, Fred D; Shao, Wen-Hai
Abstract: Endotoxin induces a variety of proinflammatory mediators and plays a crucial role in kidney inflammation. The receptor tyrosine kinase, Mer, diminishes renal inflammation by attenuating inflammatory responses. We previously reported that Mer is predominantly expressed on glomerular endothelial cells (GECs) and that Mer deficiency is associated with increased renal inflammation when mice are challenged with nephrotoxic serum. We consequently hypothesized that Mer signaling down-regulates LPS-driven inflammatory responses in GECs. To test this hypothesis, primary GECs were isolated from the kidneys of Mer-KO and wild-type (WT) control mice. LPS treatment induced Akt and STAT3 activation along with Bcl-xl up-regulation in WT GECs; these responses were all increased in Mer-deficient GECs. In addition, STAT1 and ERK1/2 up-regulation and activation were observed in Mer-KO GECs exposed to LPS. In contrast, expression of the inhibitory signaling molecule, suppressor of cytokine signaling-3 (SOCS-3), was much higher in LPS-stimulated WT than Mer-deficient GECs. Deficiency of Mer was also associated with significantly increased NF-κB expression and activation. These observations indicate that Mer functions as an intrinsic feedback inhibitor of inflammatory mediator-driven immune responses in GECs during kidney injury and suggest a new therapeutic strategy for glomerular diseases.